The Synergy between Village-Owned Enterprises and Academics in Realizing Superior and Competent Human Resources - Diovany Tirnata; Eka Yuliyanti; Anis Turmudhi (TGO Journal of Community Development, 2024)
This activity aims to develop the potential of Tanjungmojo Village through the establishment of a Village-Owned Enterprise (BUMDES), focusing on strengthening superior and competitive Human Resources (HR). The methods used include training and mentoring conducted in three main stages: preparation, implementation, and evaluation, with active participation from village officials, community leaders, and BUMDES management. The results of the activity indicate an improvement in the participants' understanding of marketing strategies, product planning, and mapping the potential of village products, as well as the use of technology to support the performance of BUMDES HR. The conclusion from this activity shows that the training has been successful in providing the necessary foundational knowledge for the formation of BUMDES, although faced with challenges in communication and the varied backgrounds of the participants. Suggestions given include the need for ongoing evaluation, aligning perceptions between organizers and participants, and discipline in following the planned schedule. This activity paves the way for the economic improvement of Tanjungmojo Village through the effective and sustainable establishment of BUMDES.